IMPROVING THE EDITORIAL POLICY TO STRENGTHEN SCIENTIFIC AND PEDAGOGICAL STAFF IN UZBEKISTAN - MADJIDOV I.U; AYRAPETYANS L.R («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article discusses the issue of strengthening the editorial policy of the international scientifc and methodological journal “Physical culture: upbringing, education, training”, by expanding the scientifc headings of the journal, conducting open scientifc trainings with gifted youth and their mentors, attracting experienced scientists from around the world to the editorial board of the journal for eﬀective work with scientifc and pedagogical staﬀ in Uzbekistan.